2011
DOI: 10.1590/s0036-46652011000100010
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-transmitted malaria: case report of asymptomatic donor harboring Plasmodium malariae

Abstract: SUMMARYMalaria in Brazil is endemic in the Amazon region, but autochthonous cases with low parasitaemia occur in the Atlantic Forest area of the country. According to Brazilian legislation no test is mandatory for blood donors from non-endemic areas. However if they have traveled to malaria transmission regions they are deferred for six months before they can donate. This report describes a transfusion-transmitted malaria case in Sao Paulo, Brazil, where one recipient received infected blood and developed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 25 publications
0
34
0
13
Order By: Relevance
“…Transmission of autochthonous malaria in SP is characterised by sporadic outbreaks in the western region (Andrade et al 1986) and persistent transmission in the eastern region, which is home to the Atlantic Forest biome; here, oligosymptomatic or even asymptomatic cases occur with low levels of parasitaemia caused by P. vivax (Carvalho et al 1985, 1988, Barata 1995, Branquinho et al 1997, Couto et al 2010) and P. malariae (Scuracchio et al 2011). The primary vector in the western region is Anopheles of the subgenus Nyssorhynchus , whereas in the eastern region, transmission occurs mainly due to Anopheles (Kerteszia) cruzii .…”
Section: Malaria In the Extra-amazonian (Non-endemic) Regionmentioning
confidence: 99%
“…Transmission of autochthonous malaria in SP is characterised by sporadic outbreaks in the western region (Andrade et al 1986) and persistent transmission in the eastern region, which is home to the Atlantic Forest biome; here, oligosymptomatic or even asymptomatic cases occur with low levels of parasitaemia caused by P. vivax (Carvalho et al 1985, 1988, Barata 1995, Branquinho et al 1997, Couto et al 2010) and P. malariae (Scuracchio et al 2011). The primary vector in the western region is Anopheles of the subgenus Nyssorhynchus , whereas in the eastern region, transmission occurs mainly due to Anopheles (Kerteszia) cruzii .…”
Section: Malaria In the Extra-amazonian (Non-endemic) Regionmentioning
confidence: 99%
“…Different tests have been used such as microscopy techniques, 50 or rapid antigen detection, 51 however, several reports have shown that PCR is, by far, the most powerful tool for such surveillance. 51,52 Such screening would prevent misdiagnoses of imported malaria cases leading to delayed treatment; would avoid unidentified reservoirs of malaria, which could contribute to local transmission and could also 53,54 avoid congenital, 55 transfusional, 56,57 or organ transplantation-associated transmission. 58,59 Our data found a prevalence of 4.6% among asymptomatic sub-Saharan Africans.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium transmission by transfusion usually occurs through whole blood and red blood cells and may occur less frequently through platelet concentrates, white blood cells, cryoprecipitate, and fresh frozen plasma [18,45]. The blood bank is therefore an important target for controlling undesirable Plasmodium transmission in endemic [38,46] and non-endemic regions [43,47]. …”
Section: Discussionmentioning
confidence: 99%